2019
DOI: 10.1088/1742-6596/1343/1/012159
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of outside view on learning: a close look to EN 17037 ‘view out’ practices through the analysis of 220 classrooms

Abstract: The purpose of design standards and guidelines is to ensure occupant safety and aid in occupant well-being and satisfaction. Educational buildings such as schools should extend this aim, by also promoting student learning, something that has triggered literature in the past suggesting significant correlation between learning performance and the indoor environment. EN 17037 “Daylight for Buildings” is a recently approved European standard that seeks to assess and ensure successful daylit spaces, including secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Several practical exercises have been carried out to assess the impact of external outlook on well-being. The standard level was assessed through the analysis of many classes [18]. The quality of lighting assessment in university classrooms is the subject of [19].…”
Section: Figurementioning
confidence: 99%
“…Several practical exercises have been carried out to assess the impact of external outlook on well-being. The standard level was assessed through the analysis of many classes [18]. The quality of lighting assessment in university classrooms is the subject of [19].…”
Section: Figurementioning
confidence: 99%
“…The timeline of the development process for both methods is shown in Figure 1. [26][27][28][29]. One of the four criteria specified in the standard for evaluating the daylighting performance of rooms is 'daylight provision', which has been an integral part of daylighting analyses for many years [30].…”
Section: Introductionmentioning
confidence: 99%
“…In order to quantify the connection between the biophilic design strategies and their impact on student and teacher performance, a thorough literature review identifying the relevant benefits of specific biophilic retrofit strategies to humans was completed and captured on the back of each strategy card. The studies found significant connections between biophilic design elements and human health and productivity outcomes, including anxiety and stress [24][25][26], attention [27][28][29][30], cognitive function [12,13,19,31], engagement (in class) [32], graduation rates [33], physical health [15,[34][35][36][37], standardized test scores [18,[38][39][40][41], systems thinking [42], teamwork [43], and thermal comfort [44].…”
Section: Introductionmentioning
confidence: 99%